Early Evolution of Transcription Systems and Divergence of Archaea and Bacteria - Lei, Lei; Burton, Zachary F. (Frontiers in Molecular Biosciences, 2021)
DNA template-dependent multi-subunit RNA polymerases (RNAPs) found in all three domains of life and some viruses are of the two-double-Ψ-β-barrel (DPBB) type. The 2-DPBB protein format is also found in some RNA template-dependent RNAPs and a major replicative DNA template-dependent DNA polymerase (DNAP) from Archaea (PolD). The 2−DPBB family of RNAPs and DNAPs probably evolved prior to the last universal common cellular ancestor (LUCA). Archaeal Transcription Factor B (TFB) and bacterial σ factors include homologous strings of helix-turn-helix units. The consequences of TFB-σ homology are discussed in terms of the evolution of archaeal and bacterial core promoters. Domain-specific DPBB loop inserts functionally connect general transcription factors to the RNAP active site. Archaea appear to be more similar to LUCA than Bacteria. Evolution of bacterial σ factors from TFB appears to have driven divergence of Bacteria from Archaea, splitting the prokaryotic domains.